Philosophy, religion, and ‘studies': scholarship as a spiritual exercise in Chinese thought - Kalmanson, Leah (Religion, 2024)
That Asian traditions do not distinguish between ‘philosophy' and ‘religion' is an oft-repeated truism. This obscures disciplinary categories operative in Asian intellectual history, especially those that do not map onto the academic landscape as we know it today. To disambiguate the terms ‘philosophy,' ‘religion,' ‘philosophy of religion,' and ‘philosophy of religious studies,' this essay explores the status of ‘studies' in Chinese thought. The tradition of rujia 儒家 or ruxue 儒學, commonly translated as ‘Confucianism,' might plausibly be rendered simply ‘scholarship.' The lineage of the ru—i.e., scholars or literati—is held together by an overarching methodology that takes the activity of studying and learning itself as a spiritual exercise aimed as scholarly excellence as well as personal cultivation. My aim is not to belabor differences between Asian and Western traditions but to invite academics to consider this rich sense of ‘studies' in our own practices today.